Multi-Level Staffing Models for Human Capital and Organisational Performance - Senapathi, R.; Varadaraj, A. (Journal of Engineering Education Transformations, 2008)
Most managers would agree that people are one of the most critical factors for business success in today 's fast-changing world . Maximizing the value of employee investment requires effective leveraging and utilizing the knowledge , skills , abilities and other characteristics (KSAOs) of you r valuable employees (Pratap Reddy, 2000).